Influence of intense training cycle and psychometric status on technical and physiological aspects performed during the small-sided games in soccer players - Selmi, O.; Marzouki, H.; Ouergui, I.; Ben Khalifa, W.; Bouassida, A. (Research in Sports Medicine, 2018)
The study investigated the effect of intense training cycle (IT) of early season preparation period (SPP) and psychological status on technical and physiological parameters during small-sided games (SSG) and the relationships between these variables. Sixteen professional soccer players participated in the study (mean±SD: age: 24.5±4.1). Training load (TL), Total quality recovery (TQR) and well-being indices were performed daily. TL increased progressively (%TL=31.56 [AU]). Physiological variables did not change after IT and were not influenced by well-being indices and TQR. Technical aspects were negatively altered after IT (p<0.05). TL was significantly correlated with successful passes (r=-0.57, p=0.02), interceptions (r=-0.83, p<0.001) and lost balls (r=0.73, p=0.002). Well-being and TQR were related to successful passes, interceptions and lost passes [(r=-0.55, p=0.03; r=-0.75, p=0.001; r=-0.69, p=0.004); (r=0.54, p=0.03; r=-0.76, p=0.001; r=-0.69, p=0.004), respectively]. TL, Well-being indices and TQR represent a useful strategy for coaches to control technical aspects in soccer players during SPP.